Effect of C-Type Natriuretic Peptide on Maturation and Developmental Competence of Goat Oocytes Matured In Vitro - Zhang, Junhong (Public Library of Science, 2015)

(untitled) (PLoS One)
The developmental competence of oocytes during in vitro maturation (IVM) is compromised due to asynchronous nuclear and cytoplasmic maturation. To improve IVM efficiency, a pre-maturation culture or two-step maturation strategy has been established, involving meiosis arrest induced by pharmacological agents to provide oocytes with sufficient time to synchronize the maturation of the nucleus and cytoplasm. C-type natriuretic peptide (CNP), which has been demonstrated to function as an oocyte maturation inhibitor (OMI) in many species, provides a new alternative to improve the developmental capacity of oocytes matured in vitro. However, the effect of CNP on meiosis arrest and the maturation of goat oocytes remains unclear. In the present study, CNP was shown to function as an OMI in goat oocytes. CNP could temporarily maintain the meiotic arrest of goat oocytes cultured in vitro for 4 hours. This transient effect was partly due to the reduction of natriuretic peptide receptor 2 (Npr2). Estradiol could delay the decrease in Npr2 expression and prolong the duration of meiosis arrest up to 6 hours. Based on the above results, a two-step method was established for goat oocyte maturation, in which the oocyte maturation rate was significantly increased. After parthenogenetic activation, the cleavage rate, blastocyst rate and total cell number of blastocysts were significantly improved. Our results suggested that CNP can be used to delay meiotic resumption and enhance the developmental competence of goat oocytes matured in vitro.